1993
DOI: 10.1111/j.1365-263x.1993.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of caries in groups of children aged 4–5 and 7–8 years in Khartoum, Sudan

Abstract: Summary. A total of 544 children, 275 pre‐school children (aged 4–5 years) and 269 school children (aged 7–8 years), were examined for dental caries using WHO criteria with some modifications. The children were resident in Khartoum, Sudan. The mean dmft was 1.68 in the 4–5‐year group, and 58% of them were caries‐free. In the 7–8‐year group the mean dmft (molars and canines) was 2.77, and 33% of the children were caries‐free. Most of the caries in both groups was untreated. In decayed teeth which were not beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
(3 reference statements)
2
10
1
Order By: Relevance
“…The pattern of dental caries in the present sample demonstrated that the prevalence of caries in the posterior teeth overall increased among the underweight and normal girls compared to the anterior teeth. The similar pattern and findings has been found from India (Mahejabeen et al, 2006) and as well as from other parts of the world (Bjarnason et al, 1995;Kerosuo & Honkala, 1991;O'Sullivan & Tinanoff, 1996;Raadal et al, 1993). This study indicates a close relationship between nutritional status and dental caries in this region.…”
Section: Resultssupporting
confidence: 74%
“…The pattern of dental caries in the present sample demonstrated that the prevalence of caries in the posterior teeth overall increased among the underweight and normal girls compared to the anterior teeth. The similar pattern and findings has been found from India (Mahejabeen et al, 2006) and as well as from other parts of the world (Bjarnason et al, 1995;Kerosuo & Honkala, 1991;O'Sullivan & Tinanoff, 1996;Raadal et al, 1993). This study indicates a close relationship between nutritional status and dental caries in this region.…”
Section: Resultssupporting
confidence: 74%
“…The prevalence of dental caries among the preschool children in the present study was high (52.4%) and the mean dmft score was 2.3. A study in Khartoum State, Sudan, only a decade ago reported a much lower dmft score of 1.68 and a more recent 2013 study in the same age group found that it had more than doubled (3.53). Whilst this may be caused by lifestyle and dietary changes, it could also be a result of different sampling criteria.…”
Section: Discussionmentioning
confidence: 95%
“…In 2003, the prevalence of dental caries in 4‐ to 5‐year‐old children in Khartoum State, Sudan, was 5.5%, with a mean decayed, missing and filled tooth (dmft) score for primary teeth of 1.68. Ten years later, in a study among 3‐ to 5‐year‐old children, a prevalence of dental caries of 65.5% with a mean dmft score of 3.53 and increased prevalence with increasing age was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Furthermore, caries prevalence and dmft value in these 8-year-old children from Qingdao were significantly higher than those reported from other countries such as Sudan. [15] The reason might be the changes in dietary habit that happened during the last decade. Changes in dietary content of the children of Qingdao have been observed in the past few years, with them consuming significantly more desserts than ever before; yet, their oral health is at a low level.…”
Section: Discussionmentioning
confidence: 99%